A escrita híbrida de História e Ficção de María Rosa Lojo – Amores Insólitos de nuestra historia (2001) – a revisitação literária de encontros históricos inusitados - Biancato, Adriana Aparecida (2018)
Based upon the hybrid history and fiction narratives, as possibilities of reinterpreting the past, we proposed a research that aimed at establishing possible approximations among a series of historical short stories selected from the book Amores Insólitos de nuestra historia (2001), by María Rosa Lojo, with the most recent theoretical approach about the mediation contemporary historical novel, which reveals the mixture of a-critical modalities - the classical and the traditional - with deconstructionist aspects – historical novels of Latin American and historiographic metafictions. In the short stories, as well as in the novels of the most recent modality, we saw a hybrid plot that Fleck (2017) classifies as being a "mediator" between traditionalism and the Latin American criticism / deconstructionism. From the point of view of Lojo's past (2001), we intend to highlight the conquest and the settlement of America through her short narratives, which privileges the expression of excluded voices, as they are not considered by the hegemonic history perspective and which, in many fictional narratives, the Argentinean identity is portrayed under the perspective of the unusual love of female protagonists. This way, we reveal about the possible actions of literature in the face of this silencing, especially, when it comes to the female voice in historiographical reports, with emphasis on the perspectives of the past recorded in the annals of history and reinterpreted by fiction. The corpus that served as the basis for this study and analysis are compound of four short stories from the selected work, being: “La historia que Ruy Díaz no escribió” (p. 45-64), “El Maestro y la Reina de las Amazonas” (p. 127-145), “Amar a un hombre feo” (p. 191-213), and “Otra historia del Guerrero y de la Cautiva” (p. 215-245). Furthermore, as inserted in studies proposals of hybrid genres of history and fiction, carried by the Research Group "Reinterpreting the past in America: processes of reading, writing and translation of hybrid genres of history and fiction - pathways to decolonization", we highlight how the characters are represented on the historical extraction of Lojo's short stories, and, we point out at the mediating aspects that constitute these narratives. The theoretical basis that allowed us to establish the relationship between the hybrid historical novel and historical short tale are anchored in studies by Aínsa (1991), Menton (1993), Fernández Prieto (2003), Esteves (2010), Fleck (2011; 2017), among others.